Management of reactive power sharing & power quality improvement with SRF-PAC based UPQC under unbalanced source voltage condition. (January 2017) - Panda, Anup Kumar; Patnaik, Nishant
Highlights: Power quality disturbing issues are addressed under non ideal conditions of supply with UPQC. Power angle control concept is used along with SRF based estimations to manage sharing of reactive power compensation. Extensive simulation and dSPACE based experimental analysis is carried out to justify the effectiveness of proposed system. Smooth and stable operation of UPQC system is observed for different transient conditions of load and voltage. Abstract: This paper is proposed to establish a new control algorithm for UPQC (unified power quality conditioner) to improve power quality and manage effectively equal reactive power sharing between shunt and series inverter of UPQC under unbalanced source voltage condition. The extraction of instantaneous power angle for reactive power sharing faces difficulty with unbalanced source voltage condition. This paper presents a new SRF (synchronous reference frame) based PAC (power angle control) method using decoupled load current parameters for efficient utilization and coordination of UPQC inverters. The proposed controller contributes in improvement of source current and load voltage harmonic profile, provides efficient way of load reactive power compensation and load voltage compensation for sag, swell and unbalanced condition. Effect of source voltage variations in the form of sag, swell or unbalancing on variable power angle estimation and reactive power calculations are also validated through a mathematical analysis. SRF based PAC control approach and PAC based UVT (unit vector template) control approach is adapted for estimating the reference signals of shunt and series inverter respectively and thus reducing the need of extra computation. The simulation and experimental analysis is carried out using Matlab/Simulink software package for computer simulation and a dSPACE based experimental setup for real time verifications.